Transcriptome Analysis of the CML Gene Family in Bletilla striata and Regulation of Militarine Synthesis Under Sodium Acetate and Salicylic Acid Treatments - Kunqian Li; Mengwei Xu; Qingqing Li; Hongwei Li; Ya Xu; Delin Xu (Plants)
Calmodulin-like proteins (CMLs) are essential for calcium signal transduction in plants, influencing growth, development, stress responses, and the regulation of medicinal secondary metabolites. Despite their importance, the roles of CML genes in B. striata have not been characterized. This study aimed to elucidate the composition and function of the BsCML gene family in B. striata, identifying 38 genes across eight subfamilies. Evolutionary analysis showed that BsCML genes are stable and conserved, while functional predictions indicated involvement in environmental stress response, hormone regulation, and circadian rhythms. Expression profiling revealed that BsCML27 and BsCML16 were highly expressed during callus culture, suggesting their involvement in growth and development. Notably, BsCML32 and BsCML37 exhibited bidirectional regulation of militarine synthesis under sodium acetate (NaAc) and salicylic acid (SA) treatments, with tissue-specific expression strongly correlated (p < 0.01) with metabolite accumulation. These findings highlight the significant roles of BsCML genes in stress response and secondary metabolite synthesis, providing a foundation for enhancing the medicinal quality of B. striata.